2016
DOI: 10.1080/17469899.2016.1180246
|View full text |Cite
|
Sign up to set email alerts
|

What rates of glaucoma progression are clinically significant?

Abstract: Summary Clinically important rates of glaucoma progression (worsening) are ones that put a patient at risk of future functional impairment or reduction of vision-related quality of life. Rates of progression can be evaluated through measuring structural or functional changes of the optic nerve. Most treated eyes do not progress at rates that will lead to future visual impairment, but there are a significant proportion (3-17%) of eyes, that are at risk of impairment even under clinical care. While very fast rat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
44
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 66 publications
(46 citation statements)
references
References 113 publications
(113 reference statements)
1
44
0
1
Order By: Relevance
“…This is in agreement with a recent report indicating that 3–17% of known and treated glaucoma patients are at risk for advanced visual impairment within 20 years (Saunders et al. ). Further, the clinical relevance of the current choice of loss rate is supported by retrospective studies on known and treated glaucoma patients.…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…This is in agreement with a recent report indicating that 3–17% of known and treated glaucoma patients are at risk for advanced visual impairment within 20 years (Saunders et al. ). Further, the clinical relevance of the current choice of loss rate is supported by retrospective studies on known and treated glaucoma patients.…”
Section: Discussionsupporting
confidence: 94%
“…Rapid detection of ONH and/or RNFL changes enables prompt adjustment of treatment which can reduce the rate of progression. Currently, known and treated glaucoma patients still risk advanced visual impairment or blindness during their lifetime (Peters et al 2014;Saunders et al 2016). Hence, rapid detection of glaucoma progression is desirable.…”
Section: Introductionmentioning
confidence: 99%
“…This is because standard structural measures have a limited dynamic range as they thin with advanced OAG, and visual field (VF) test points are more variable in advanced disease. 10 16 Complicating matters further, recent reimbursement criteria in the United States have limited the use of imaging in advanced OAG 17 because VF testing is considered more diagnostic in advanced disease.…”
mentioning
confidence: 99%
“…Nevertheless, monitoring advanced glaucoma using standard structural and functional testing is extremely difficult for the treating clinician because both standard structural and functional tests that usually guide treatment decisions are of diminished value. Standard structural measures have a limited dynamic range and visual field (VF) test points are more variable in advanced disease [81,[115][116][117][118][119][120]. However, Belghith et al have shown that even in very advanced glaucoma, structural loss can be detected in some eyes using standard global structural measures with macular GCIPL identifying the highest proportion of eyes with detectable change, followed by MRW and cpRNFL [121].…”
Section: Detection Of Glaucomatous Progression With Octmentioning
confidence: 99%